Profits too high? Assessing inflation in the eurozone using wage and price rules for profit and unit labor costs based on national accounts data - Heike Joebges; Camille Logeay (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2024)
The strong increase in inflation rates in Europe at the end of 2022 is in stark contrast to more than a decade of very low developments within the euro area. This time, profit hikes are under more scrutiny than wage increases. As changes in profits in relation to those of wages have the potential to change the functional income distribution, we analyse past and current price developments by decomposing the contributions to domestic prices, measured by the GDP deflator, into those stemming from unit labour costs, those from unit profits, and those from net unit taxes on production. In order to judge those developments as stability-oriented or not, we follow the literature that recommends that national wage developments should be in line with the inflation target of the ECB plus the increase in labour productivity. Such a development, if also applied to profits, would not kick-start an inflationary process and would support a stable functional income distribution. Our descriptive analysis covers annual inflation contributions from unit labour costs and unit profits from 1999 to 2023 in 19 countries of the Euro Area. According to our results, developments have been heterogeneous among the studied countries since the introduction of the euro and continue to show differences in price developments. Yet, it is striking that unit profit increases have recently been far above levels observed in the past in all member countries, and are higher than for unit labour cost increases. Even if it is too early to ignore the possibility of only temporary cyclical profit developments, unit profit developments cannot be explained by developments of GDP, interest rates and terms-of-trade according to our out-of-sample forecast. Yet, more detailed data is necessary for explaining the factors behind this increase in unit profits at an aggregate level.
Keywords: E25; E31 E64; F45; 330; nflation; GDP deflator; functional income distribution; wage rule; profit rule; gross operating surplus; unit labour costs